Grand Canonical ReaxFF Molecular Dynamics Simulations for Catalytic Reactions - Jung, Christoph K; Braunwarth, Laura; Jacob, Timo (Journal of chemical theory and computation, 2019)
In order to study the time-dependent behavior of catalytic systems during operation, we have developed a grand canonical molecular dynamics approach based on the ReaxFF reactive force-field framework. After describing the details of the implementation, the capabilities of this method are demonstrated by studying the gas-phase water formation from oxygen and hydrogen on platinum catalysts during the steady state where we discuss the effects of the surface structure as well as the importance of kinetics. The approach presented here can be extended to other dynamic (catalytic) systems, providing a framework for exploring catalytic and electrocatalytic processes, in particular, allowing studies on the effects of reaction conditions on a system’s behavior, characteristics, and stability.